Study on the Consideration of Mental Symptoms in Constituting Totality of Symptoms through Case Study on Migraine (Advancements in Homeopathic Research, 2022)
Homoeopathy is a therapeutic science that treats the patient and not the disease. The true Homoeopathic cure takes place only when there is selection of the remedy, most similar to the case of disease. The selection of the most similar remedy is chiefly determined by the ‘Totality of Symptoms.’ From the time of Dr. Hahnemann ‘Mental Symptoms’ are considered to be of prime importance in the constructing the ‘Totality of Symptoms’. All the stalwarts, masters and prescribes have emphasized on the importance of ‘Mental Symptoms’ in constructing the ‘Totality of Symptoms’, but only a fraction of practitioners and therapists till date have been reported to give due importance to the Mental Symptoms & Mental State during practical case taking to utilize them for construction of ‘Totality of Symptoms’. Thus, a need for study of exploring consideration of Mind as central point becomes necessary. This case study on Migraine will help us in understanding the importance of Mental Symptoms and the Mental State of the patient in Homoeopathic prescription, so as to use that information for a deeper understanding of the cases, resulting in a better prescription.
Keywords: Migraine; Mental; Homoeopathic; Symptoms